Electrochemical and in situ spectroelectrochemical investigations into the redox and aggregation behaviours of phthalocyanines bearing octyl 4-phenyloxyacetate moieties - (:unkn) unknown (CANADIAN SCIENCE PUBLISHING, NRC RESEARCH PRESS, 2010)
Electrochemical and spectroelectrochemical properties of phthalocyanines (H(2)Pc, ZnPc, NiPc, CuPc, and CoPc) involving octyl 4-phenyloxyacetate moieties have been investigated by cyclic voltammetry and differential pulse voltammetry on Pt in dimethylsulfoxide - tetrabutylammonium perchlorate. These measurements showed that the complexes undergo subsequent one-electron reduction and oxidation processes. In situ UV-vis spectroelectrochemical measurements enabled us to identify the ligand- and metal-based redox processes, and evaluate the effect of aggregation phenomena on these processes. The cobalt complex showed both metal-based and ring-based one-electron redox processes, while the other complexes displayed only ring-based one-electron couples. It was observed that the redox processes of H(2)Pc, NiPc, and CuPc are coupled by aggregation phenomenon, whereas those of ZnPc and especially CoPc are not, probably owing to the difference in their axial coordinating properties.
Keywords: phthalocyanines; aggregation; electrochemistry; in situ spectroelectrochemistry; PHOTOPHYSICAL PROPERTIES; COBALT PHTHALOCYANINES; METAL PHTHALOCYANINES; REDUCTION; METALLOPHTHALOCYANINES; TETRASULFONATE; SUBSTITUENTS; DERIVATIVES; ALUMINUM; SOLVENT